EVALUASI TATA KELOLA TEKNOLOGI INFORMASI DENGAN MENGGUNAKAN KERANGKA COBIT 4.0 DOMAIN DS (Delivery and Support) DAN ME (Monitoring Evaluation) : STUDI KASUS PT PRO CAR INTERNATIONAL FINANCE JAKARTA - Lita Sari Marita; Yan Riyanto (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
Utilization of IT has been providing solutions and benefits through the opportunities as a form of the strategic role of IT in achieving its vision and mission. Opportunities created from the optimization of IT resources on areas of company resources including data, application systems, infrastructure, and human resources. On the other hand, IT implementation requires a relatively expensive investment cost, where the emergence of the risk of failure is also quite large. This condition requires consistency within the field of management, so an IT Governance (IT Governance) that is suitable will be an essential requirement. To achieve this we need management of existing IT structured. IT Governance Institute (ITGI) defines IT governance as a responsibility of executive and board of directors, and consists of leadership, organizational structures, and processes that ensure IT companies to support and expand the organization's objective and strategy. IT governance objectives are to be able to direct the efforts of IT, thereby ensuring IT performance according to the fulfillment of the following objective: 1. IT aligned with the company and the realization of promised benefits. 2. Using IT enables companies to exploit opportunities and maximize benefits. 3. The use of IT resources is responsible. Proper management of risks related to IT. COBIT is one methodology that provides the basic framework in creating appropriate information technology with organizational needs while considering other factors that influence. This thesis took DS and ME domain of COBIT framework, determine the maturity of the Corporate Governance Ti Pro Car International Finance, Jakarta, and then provide recommendations. Currently IT Governance Maturity PT. International Car Finance Jakarta is at Level 3 and level 4 is expected to become the Company has established a number of indicators or quantitative measures that serve as the target or objective performance of each application of the existing information technology applications. It is expected that the research can be conducted periodically, either in the same plane or different.